Etnomathematic Analysis: Implementation Of The Ecentric Digraph In Determining The Ka'ba As Center Of The Earth - Marwah Daud Wijayanti; Detalia Noriza Munahefi; Kristina Wijayanti; Agung Prabowo (International Journal of Ethno-Sciences and Education Research, 2022)
The Rajaban tradition is a tradition of religious rituals as an expression of gratitude and moments to commemorate historical events, one of which is the change in the direction of Qibla from Baitul Maqdis to the Kaaba in Mecca. Based on these problems, in this article, it is shown by using the study of Graph Theory, namely the eccentric digraph to determine the center of the earth's region. Data processing is done by making the Kaaba and the seven continents on the earth's surface as a point on graph G and the side connecting the points is the distance (in km) with physical boundaries between them being considered non-existent. The results of the discussion show that the Kaaba in Mecca is the center of the earth's area with ec(v1) = 12,039 = rad(G).